أثر نظام المعلومات على تحلیل العلاقات الاقتصادیة بین المؤشرات - الناتج المحلي والإنتاج الصناعي في الجزائر - هیشر أحمد تجاني; غانیة نذیر (Finance and Business Economies Review, 2018)
The industrial information system in the structure of the statistical authority reflects the extent of the state's culture in the interest of the growth of its economy because of the industrial information in providing data on economic indicators. This is an interest in the developed countries. The countries are volatile. The information systems of the countries are poor from the recent data and if they are flawed, they are contradictory to the economic theory, making the researcher difficult to analyze and interpret their results and find it difficult to model them within a mathematical law. In this work, we tried to know the status of the industrial information in the Algerian economy. We took the GDP and IND indices in Algeria during the period 1970-2015, so we used the data of the World Bank for the indicators of the Algerian economy and the Algerian National Statistics Bureau ONS. With these data we examined the economic relationship between the two variables. The results of the joint integration test showed a long-term equilibrium relationship with a one-way GDP to IND short- and long-term causality. This result is not consistent with the economic theory called the Caldor hypothesis.